Analysis of Students' Psychomotoric Abilities in Daily Life -Based Practicum on Reaction Rate Material - Fadzliana, Nanda; Kurniawati, Yenni (Journal of Educational Chemistry (JEC), 2024)
The aim of this research is to analyzing students' psychomotor abilities in daily life -based practicums on reaction rate material. This research was carried out in the 2022/2023 academic year at Madrasah Aliyah Negeri 1 Kampar with the material Reaction Rate. The method used in this research is quantitative descriptive. The instruments used in this research were performance assessment sheets to determine students' psychomotor abilities and interviews to strengthen the data obtained. The results of data analysis show that the average psychomotor ability of students is 79.19. The highest average score obtained was in the naturalization domain with the very good category and the psychomotor ability with the lowest average score obtained was in the precision domain with the good category. The psychomotor indicator with the highest average score is assembling experimental equipment in the very good category, and the psychomotor indicator with the lowest average score is the indicator for splitting and smoothing solid substances in the good category. The psychomotor abilities of the students are mostly in the good category, which is 52% with the highest rating scale score being scale 4 with a good category, which is 59%. Daily life -based chemistry practical learning can make it easier for students to carry out practical work.